Help-Seeking and Help-Outreach Intentions of Healthcare Workers—The Role of Mental Health Literacy and Stigma in the Workplace - Wulf, Ines Catharina (Frontiers in Education, 2022)
Due to the demanding work environment, health care workers are often affected by mental health problems. Besides negative effects on individual well-being, mental health problems can reduce professional effort and increase turnover rates in health care. Those who develop mental health problems often receive necessary treatment with a great time delay. Two reasons for this are low mental health literacy and stigma. However, empirical investigations regarding the role of workplace mental health literacy and stigma on help-seeking and help-outreach intentions of health care workers in the workplace are currently missing. To bridge this gap, survey data was collected among trainees of different health care professions in Germany. The variables of interest were measured separately with the help of two times of measurement to avoid common method bias and to strengthen the causal interpretability of the hypothesized model. The response rate of the questionnaire was 21 % (Nt1 = 525, Nt2 = 112). For measuring subjective mental health literacy at the workplace the MHL-W-G was used. Results of the structural equation modelling (SEM) indicate that workplace mental health literacy increases workplace help-seeking intention and help-outreach intention significantly. Further, it indicates that workplace mental health literacy decreases self-stigma and that personal stigma decreases overall workplace help-outreach intention. In order to uncover underlying mechanisms of the relationship between the mental health literacy and workplace help-seeking intention and help-outreach intention, the mediation of mental health stigma was tested, but could not be confirmed. The present study reduces the lack of empirical information regarding mental health help-seeking and help-outreach in the workplace. Therefore, the research contributes to the relevance of social contacts in the working context as potential gatekeepers to professional mental health support. Further, the study provides important insights into the way that mental health help-seeking and help-outreach intentions at the workplace are affected by mental health literacy and into the role of personal and self-stigma in health care profession. The results are of particular importance in light of the increased need for health care workers and the rising prevalence of mental diseases.